2021
DOI: 10.31603/ae.4569
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effect of Nano Additives γAl2O3 and Equivalence Ratio to Bunsen Flame Characteristic of Biodiesel from Nyamplung (Calophyllum Inophyllum)

Abstract: Nano γAl2O3 has been one of the nanometal oxides that has improved the characteristics of biodiesel. The effect of γAl2O3 nanoparticles addition on premixed flame combustion is investigated with an experiment on the laminar flame speed of Calophyllum inophyllum methyl ester 30% and 70% petrodiesel mixtures, at atmospheric pressure and preheated temperature T = 473K. The γAl2O3 nanoparticles added to CIME30 biodiesel were 0ppm, 100ppm, 200ppm, and 300ppm. Experiments were carried out on a bunsen burner. The equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…From the data presented, it can be observed that non-magnetic B100 fuel has the lowest combustion speed on average, while B0 fuel has the highest combustion speed in all variations of the equivalent ratio. This is because the B100 fuel has a higher viscosity and density than B0 fuel, causing the fuel to evaporate more difficult and the combustion to be less than optimal [9], [20]. Under the influence of a magnetic field, the laminar burning velocity of B100 fuel has increased at all variations of the magnetic poles.…”
Section: Analysis Of Laminar Burning Velocity (Sl)mentioning
confidence: 99%
See 1 more Smart Citation
“…From the data presented, it can be observed that non-magnetic B100 fuel has the lowest combustion speed on average, while B0 fuel has the highest combustion speed in all variations of the equivalent ratio. This is because the B100 fuel has a higher viscosity and density than B0 fuel, causing the fuel to evaporate more difficult and the combustion to be less than optimal [9], [20]. Under the influence of a magnetic field, the laminar burning velocity of B100 fuel has increased at all variations of the magnetic poles.…”
Section: Analysis Of Laminar Burning Velocity (Sl)mentioning
confidence: 99%
“…Increasing the average unsaturation helps to improve the low-temperature performance but creates some negative effects such as decreased cetane number and poor oxidation stability [8]. Biodiesel C. Inophyllum has a higher density, viscosity, and flash point than diesel oil [9]. The high viscosity of the fuel causes carbon deposits on the fuel filter, injectors, and piston rings [10].…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate the challenges posed by fossil fuels, renewable fuels like biodiesel from different feedstocks are gaining wide popularity nowadays more than ever (Kolakoti et al, 2021;Kolakoti, Prasadarao, et al, 2021;Pambudi et al, 2021;Setiyo et al, 2021;Sule et al, 2022;Supriyadi et al, 2022). Several researchers (as shown in Table 1) are inclined toward biodiesel utilization due to their exceptional capability in lowering harmful exhaust emissions and, at the same time conquering fuel scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel can be produced from either edible or non-edible feedstock. Examples of feedstock used in the production of biodiesel include karanja, palm, soybean, canola, sunflower, jatropha, rapeseed, etc [6]- [9]. Biodiesel can be produced via the transesterification process in which triglycerides from feedstocks react with alcohol in the presence of a catalyst [10]- [16].…”
Section: Introductionmentioning
confidence: 99%